Food insecurity, childhood hunger and caregiver life experiences among households with children in South Carolina, USA. Issue 14 (17th May 2019) - Drucker, Erin R; Liese, Angela D; Sercy, Erica; Bell, Bethany A; Draper, Carrie; Fleischer, Nancy L; Flory, Kate; Jones, Sonya J
Abstract: Objective: We explored how positive and negative life experiences of caregivers are associated with household food insecurity. Design: The Midlands Family Study (MFS) was a cross-sectional study with three levels of household food security: food secure, food insecure without child hunger and food insecure with child hunger. Ordinal logistic regression analysis was used for analyses of negative and positive life experiences (number, impact, type) associated with food insecurity. Setting: An eight-county region in South Carolina, USA, in 2012–2013. Participants: Caregivers ( n 511) in households with children. Results: Caregivers who reported greater numbers of negative life experiences and greater perceived impact had increased odds of household food insecurity and reporting their children experienced hunger. Each additional negative life experience count of the caregiver was associated with a 16 % greater odds of food insecurity without child hunger and a 28 % greater odds of child hunger. Each one-unit increase in the negative impact score (e.g. a worsening) was associated with 8 % higher odds of food insecurity without child hunger and 12 % higher odds of child hunger. Negative work experiences or financial instability had the strongest association (OR = 1·8; 95 % CI 1·5, 2·2) with child hunger. Positive life experiences were generally not associated with food security status, with one exception: for each unit increase in the number of positive experiences involving family and other relationships, the odds of child hunger decreased by 22 %. Conclusions: More research is needed to understand approaches to build resilience against negative life experiences and strengthen positive familial, community and social relationships.